An Ideal Model for The Preparation of Internal Regulations of Universities in Indonesia Based on Meaningful Participation in The Success of Sustainable Development Goals (SDG's) 2030 - Sulaksono; Sulistyowati, Eny; Ali Masnun, Muh.; Yahya, Najeeb (Jurnal Suara Hukum, 2025)
This research aims to offer an ideal model for the formulation of internal regulations in higher education institutions based on the concept of meaningful participation in achieving the SDGs. This research is a normative legal study that emphasizes a conceptual, legislative, and case approach. The research results affirm that internal regulations of higher education institutions are part of the hierarchy of national legislation. The urgency of implementing meaningful participation in the formulation of internal regulations at higher education institutions is expected to realize the sixteenth goal of the SDGs, which is to create resilient institutions. This way, internal regulations at higher education institutions can be formulated effectively by considering needs and prioritizing legal harmonization with other regulations. The ideal model for the formation of internal regulations in higher education institutions needs to be based on transparency aspects related to planning, supervision, implementation, and evaluation, which must accommodate three aspects of meaningful participation, namely the right to be heard, the right to be considered, and the right to be explained. In addition, to ensure legal certainty, specific regulations need to be formulated at the national level that provide general guidelines related to the formation and drafting of legal products for higher education institutions, which will then be followed up with technical regulations within each higher education institution.